The effect of architecture of Cu/Ni-Cu multilayer coatings on their microhardness - Maizelis, A.A.; Bairachniy, B.I.; Trubnikova, L.V.; Savitsky, B.A. (Functional Materials, 2012)
The results of measuring of the microhardness of Cu/(Ni-Cu) multilayer coatings are reported. These coatings were deposited from the pyrophosphate-ammonium electrolyte. It is shown that the microhardness of the multilayer coatings strongly depends on their architecture, as long as coatings were formed from the layers under the identical optimal conditions. The microhardness reaches its maximum when the bilayer thickness is in the range of 40-60 nm and the Ni-Cu and Cu layers thicknesses ratio is in the range of 1.8-2.5. For each layer thickness ratio, the microhardness has the maximum at its own bi layer thickness range.